Light‐Liquid Selective Filters: Light‐Liquid Selective Filter‐Mounted Nanowire‐Networked Polyurethane Fiber for an Ultraviolet Sensor (Adv. Mater. Interfaces 19/2019). Issue 19 (9th October 2019) - Lim, Taekyung; Jung, Sang‐Mi; Kang, Youngsoo; Ju, Sanghyun
Abstract : The SnO2 nanowire‐networked polyurethane fiber covered with a (1 H, 1 H, 2 H, 2 H ‐heptadecafluorodec‐1‐yl) phosphonic acid‐coated Al2 O3 nanoparticles can stably detect ultraviolet intensity even when exposed to liquids. More details can be found in article number 1901015 by Taekyung Lim, Sanghyun Ju, and co‐workers.